New beaked whales from the late Miocene of Peru and evidence for convergent evolution in stem and crown Ziphiidae (Cetacea, Odontoceti) - Giovanni Bianucci (PeerJ, 2016)
The Ziphiidae (beaked whales) represent a large group of open-ocean odontocetes (toothed cetaceans), whose elusive and deep diving behavior prevents direct observation in their natural habitat. Despite their generally large body size, broad geographical distribution, and high species number, ziphiids thus remain poorly known. Furthermore, the evolutionary processes that have led to their extreme adaptations and impressive extant diversity are still poorly understood. Here we report new fossil beaked whales from the late Miocene of the Pisco Formation (southern Peru). The best preserved remains here described are referred to two new genera and species, the Messinian Chavinziphius maxillocristatus and the Tortonian Chimuziphius coloradensis, based on skull remains from two marine vertebrate-rich localities: Cerro Los Quesos and Cerro Colorado, respectively. C. maxillocristatus is medium sized retains a complete set of functional lower teeth, and bears robust rostral maxillary crests similar to those of the extant Berardius. By contrast, C. coloradensis is small and characterized by large triangular nasals and moderately thickened premaxillae that dorsally close the mesorostral groove. Both species confirm the high past diversity of Ziphiidae, the richest cetacean family in terms of the number of genera and species. Our new phylogenetic and biogeographical analyses depart markedly from earlier studies in dividing beaked whales into two major clades: the Messapicetus clade, which, along with other stem ziphiids, once dominated the southeastern Pacific and North Atlantic; and crown Ziphiidae, the majority of which are found in deep-water regions of the Southern Ocean, with possible subsequent dispersal both globally (Mesoplodon and Ziphius) and to the cooler waters of the northern oceans (Berardius and Hyperoodon). Despite this relatively clear separation, both lineages seem to follow similar evolutionary trends, including (1) a progressive reduction of dentition; (2) an increase in the compactness and thickness of the rostral bones; (3) similar changes in facial morphology (e.g., elevation of the vertex); and (4) an increase of body size. We suggest that these trends may be linked to a convergent ecological shift to deep diving and suction feeding.